Anthocyanins decrease the internalization of TiO2 nanoparticles into 3D Caco-2 spheroids. (30th November 2020) - Wang, Junkang; Zhang, Jiaqi; Li, Shuang; Huang, Chaobo; Xie, Yixi; Cao, Yi
Highlights: Anthocyanins reduced TiO2 NPs internalization into 3D Caco-2 spheroids. Anthocyanins only minimally changed the colloidal properties of TiO2 NPs. TiO2 NPs and anthocyanins minimally induced cytotoxicity or oxidative stress. NP internalization was inversely correlated with the binding affinity. TiO2 NPs and anthocyanins up-regulated some types of ABC transporters. Abstract: The influence of food components on nanoparticle (NP) internalization indicates a need to investigate the behaviors of NPs in a complex system. This study measured the changes of TiO2 NP colloidal stability and quenching of anthocyanin fluorescence to indicate NP-anthocyanin interactions, and cytotoxicity, oxidative stress, expression of ABC transporters and intracellular Ti concentrations in 3D Caco-2 spheroids co-exposed to NPs and anthocyanins to indicate the influence of anthocyanins on NP bio-effects. The anthocyanins were observed to have minimal impacts on colloidal properties of TiO2 NPs. Meanwhile, NP-anthocyanin co-exposure did not induce cytotoxicity or oxidative stress. The fluorescence quenching study indicated the binding of anthocyanins onto TiO2 NPs, and the binding affinity was inversely correlated with NP internalization into 3D Caco-2 spheroids. This may be partially related with the up-regulation of ABC transporters. Our results may provide novel insights into understanding the interactions of NPs and anthocyanins with human intestinal cells.